Effect of different artificial diets on the adults biological attributes of sugarcane stalk borer, Chilo auricilius Dudgeon and evaluation of their costs (Journal of Applied and Natural Science, 2015)
An experiment was conducted to evaluate the effect of different artificial diets on the adult’s biological attributes of sugarcane stalk borer (Chilo auricilius Dudgeon) and their costs. Considering the mean values of first and second generation the maximum adult emergence (80.66 and 79.25), longer adult longevity (4.29 and 4.28), highest fecundity (233.45 and 225.98) and viability of egg (216.25 and 208.74) was recorded on diets A and C. Also the sex-ratio on diets A (M:F::1:1.16) and C (M:F::1:1) favoured the emergence of more number of females thanmales during development. On the basis of the economics also the artificial diets D, C and A (Rs. 48.62, Rs. 48.32, Rs. 103.43, respectively) were found relatively cheaper than the natural food (Rs 166.67). Thus, the overall performance of C. auricilius on diets A and C was found comparatively better than the other diets examined. Therefore, it can be used as an alternate diet other than natural diet E (sugarcane) for the mass rearing of C. auricilius in the laboratory.